Transformasi Literasi Fisik pada Siswa Sekolah Dasar di Indonesia: Intervensi Sport Education Models (SEM) Selama 8 Minggu - Wicaksana, Amrih Ibnu; Nurhasan, Nurhasan; Kristiyandaru, Advendi (Ilmu Olahraga, 2025)
Physical literacy, encompassing motivation, self-confidence, motor skills, and knowledge for lifelong active participation, remains low among Indonesian elementary school students: less than 40% meet competency standards, and more than 70% do not achieve 60 minutes of daily activity.In a randomized controlled trial in Jombang, East Java, 120 fourth–sixth grade students were divided into two groups. The intervention group participated in an eight-week Sports Education Model (SEM) (two 45-minute sessions per week) with role assignments, mini-tournaments, reflection, and discussion; the control group underwent a conventional curriculum. Physical literacy was measured using a validated instrument before and after the program.Results showed an average increase in the physical literacy score of the SEM group of 8.24 points (p<0.001). However, after adjusting for confounding variables, the difference between groups was not significant (F(1,116)=0.187; p=0.667). Retrospective bias occurred: post-test scores significantly predicted pre-test scores (η²=0.138; p<0.001), indicating that intervention experience influenced self-evaluations of initial abilities.SEM has been shown to potentially improve physical literacy, but its eight-week duration may not be sufficient for significant differences between groups. Future studies are recommended to extend the intervention to 12–16 weeks, include structured teacher training, and use a multicenter longitudinal design to strengthen evidence of effectiveness and ensure sustainability.